Investigation of tumor hypoxia using a two-enzyme system for in vitro generation of oxygen deficiency - Askoxylakis, Vasileios; Millonig, Gunda; Wirkner, Ute; Schwager, Christian; Rana, Shoaib; Altmann, Annette; Haberkorn, Uwe; Debus, Jürgen; Mueller, Sebastian; Huber, Peter E. (Radiation oncology, 2011)
Oxygen deficiency in tumor tissue is associated with a malign phenotype, characterized by high invasiveness, increased metastatic potential and poor prognosis. Hypoxia chambers are the established standard model for in vitro studies on tumor hypoxia. An enzymatic hypoxia system (GOX/CAT) based on the use of glucose oxidase (GOX) and catalase (CAT) that allows induction of stable hypoxia for in vitro approaches more rapidly and with less operating expense has been introduced recently. Aim of this work is to compare the enzymatic system with the established technique of hypoxia chamber in respect of gene expression, glucose metabolism and radioresistance, prior to its application for in vitro investigation of oxygen deficiency.
Gesehen am 23.03.2022